(untitled) (Community Based Medical Journal, 2015)
Pediatric high dependency care (PHDC) is a care comprising of close observation, monitoring and management of children who are vulnerable to physiological instability. To determine the pattern of admission and register outcome of patients in the pediatric high dependency care (PHDC) of Dhaka Shishu( Children) Hospital, a tertiary level referral children hospital in Bangladesh. This is a retrospective study of the record of patients admitted to the PHDC unit at the Dhaka Shishu Hospital from May 2015 to February 2016. The information obtained from the admission/discharge record as well as the patients’ case notes included demographic data, working diagnosis, type of management, length of stay (LOS) in the PHDC unit and outcome. A total of 140 children were admitted during the study period comprising of 80 (57.15%) males and 60 (42.85%) females, giving a male: female ratio of 1.33:1. The age ranged from one day to 12 years with a mean of 35.44±3.1 months. Meningitis (both bacterial and viral) accounted for 24 (17.14%) followed by encephalitis, 21 (15%) were the major indications for admission. Other indications included seizure disorders (both febrile and afebrile), 18 (12.85%); bronchopneumonia including acute bronchiolitis, 15 (10.71%); neonates with different indications 13(9.28%); typhoid fever with complications 5 (3.57%); mumps with complications, 4(2.85%); chickenpox with complications, 3(2.14%); surgical conditions, 7 (5%), and others, 30(21.42%). There were no post-operative surgical cases. The length of stay (LOS) in the unit ranged from 1 day to 34 days with mean of 7.9±0.5 days. The treatment expenses ranged from 1000 BDT to 50,000 BDT with a mean of 12297.14±888.69 BDT. Out of total 140 admissions, 82 (58.57%) were discharged in a satisfactory condition; discharge on request (DOR), 30 (21.42%); referred to intensive care unit (ICU), 7 (5%); left against medical advice (LAMA), 15(10.71%) and death, 6 (4.2%); case fatality rate (CFR), 4.2/100 admission. Among the death cases there were 2 meningitis, 2 encephalitis, 1 acute bronchiolitis and 1 preterm very low birth weight (VLBW). Meningitis, encephalitis, bronchopneumonia, seizure disorder were the major causes of admission in PHDC unit, while case fatality was the highest for meningitis and encephalitis. Therefore, awareness regarding prevention, early detection and management of meningitis and encephalitis should be emphasized. CBMJ 2015 July: Vol. 04 No. 02 P: 27-30